Mechanism Based Quality Control (MBQC) of Herbal Products: A Case Study YIV-906 (PHY906) - Lam, Wing; Ren, Yongshen; Guan, Fulan; Jiang, Zaoli; Cheng, William; Xu, Chang-Hua; Liu, Shwu-Huey; Cheng, Yung-Chi (Frontiers in Pharmacology, 2018)
YIV-906(PHY906), a four-herb Chinese medicine formulation, is inspired by an 1800 year-old Chinese formulation called Huang Qin Tang which is traditionally used to treat gastrointestinal (GI) symptoms. In animal studies, it could enhance anti-tumor activity of different classes of anticancer agents and promote faster recovery of the damaged intestines following irinotecan or radiation treatment. Several clinical studies have shown that YIV-906 had the potential to increase the therapeutic index of cancer treatments (chemotherapy, radiation) by prolonging life and improving patient quality of life. Results of animal studies demonstrated five clinical batches of YIV-906 had very similar in vivo activities (protection of body weight loss induced by CPT11 and enhancement of anti-tumor activity of CPT11) while four batches of commercial–made Huang Qin Tang, HQT had no or lower in vivo activities. Two quality control platforms were used to correlate the biological activity between YIV906 and HQT. Chemical profiles (using analysis of 77 peaks intensities) obtained from LC-MS could not be used to differentiate YIV-906 from commercial Huang Qin Tang. A Mechanism Based Quality Control (MBQC) platform, comprising 18 luciferase reporter cell lines and two enzymatic assays based on the mechanism action of YIV-906, could be used to differentiate YIV-906 from commercial Huang Qin Tang. Results of MBQC could be matched to their in vivo activities on irinotecan. In conclusion, the quality control of an herbal product should be dependent on its pharmacological usage. For its specific usage appropriate biological assays based on its mechanism action should be developed for QC. Chemical fingerprints to differentiate formulations has limitations unless irrelevant chemicals have been filtered out. Additionally, using a similarity index is only useful when relevant information is used. A MBQC platform should also be applied on other herbal products.